"Teachers Don't Really Encourage it": A Critical Race Theory Analysis of High School Students' of Color Perceptions of the Teaching Profession. (2nd January 2021) - Marrun, Norma A.; Plachowski, Tara J.; Mauldin, De'Ana R.; Clark, Christine
ABSTRACT: Seeking to enhance efforts to diversify the teaching profession, this article centers the educational experiences of high school Students of Color. Using a Critical Race Theory framework, this study examines the relationship between Students' of Color school experiences and their perceptions of the teaching profession. Findings reveal that these students perceive the teaching profession as a boring, undervalued, and white profession, and that conversations about pursuing college and exploring a career in teaching are absent from the classroom or presented as only the purview of white students. Race conscious recommendations to encourage and support Students of Color to pursue college and to explore a teaching career are presented.